Interpretation of Analogy in the Crime of Possession of a New Psychoactive Substance - Zhafirah, Carissa Tita; Noerdajasakti, Setiawan; Madjid, Abdul (Jurnal Magister Hukum Udayana (Udayana Master Law Journal); Vol 14 No 2 (2025)DO - 10.24843/JMHU.2025.v14.i02.p02, 2025)
This study aims to analyze the application of analogy interpretation by judges in the case of possession of new psychoactive substances, especially in Decision Number 1352/Pid.Sus/2024/PN Mdn on behalf of the Defendant Lindawati. The background of this research departs from the delay of the Indonesian legal system in responding to social changes, especially related to the phenomenon of the spread of new psychoactive substances that have not been explicitly regulated in laws and regulations. This study uses a normative juridical method with a legislative approach, a case approach, and a conceptual approach. Analysis was carried out on primary, secondary, and tertiary legal materials using anticipatory and teleological interpretation methods. The results of the study showed that the Panel of Judges used Article 62 of the Psychotropic Law to punish the Defendant, even though the substance ketamine was not listed in the official psychotropic appendix. This action reflects the findings of the law through analogy, which is doctrinally contrary to the principle of legality in criminal law. Nevertheless, from a progressive legal perspective, the application reflects a response to rapidly changing social realities as well as the need for adaptive legal protection. This study concludes that although analogies in criminal law are prohibited, their application in the context of a legal vacuum for psychoactive substances can only be understood as an effort to realize substantive justice and public protection through a progressive approach in criminal law enforcement. Keywords: New Psychoactive Substances; Legal Discovery; Analogy